Distribution of Dehalococcoidia in marine sediments and strategies for their enrichment ... : Verteilung von Bakterien der Klasse Dehalococcoidia in marinen Sedimenten und Strategien für ihre Anreicherung ... - Algora, Camelia (Technische Universität Berlin, 2016)
The marine subsurface is one of the largest microbial habitats on Earth. Microbial community studies based on the 16S rRNA gene have revealed that bacteria of the class Dehalococcoidia, phylum Chloroflexi, are one of the most widespread and abundant bacteria inhabiting the marine subsurface. However, their physiology and ecological role are unknown. In this study, marine sediments were cultivated with various potential electron acceptors to explore respiration modes catalysed by Dehalococcoidia. The cultivation revealed that Dehalococcoidia can be cultivated in an anoxic minimal medium amended with hydrogen and acetate as potential electron donor and carbon source, respectively, at a temperature of 30ºC and at atmospheric pressure, and thus Dehalococcoidia are not strict piezophilic bacteria. An increase in Dehalococcoidia 16S rRNA gene copy numbers of one order of magnitude, as evidenced by quantitative PCR with newly designed primers, could be observed in a time span of months for several sediment ... : Marine Sedimente sind einer der größten mikrobiellen Lebensräume der Erde. 16S rRNA-basierte Studien der mikrobiellen Gemeinschaften haben gezeigt, dass Bakterien der Klasse Dehalococcoidia des Phylums Chloroflexi ubiquitär und abundant in marinen Sedimenten vorkommen. Die Physiologie und ökologische Funktion dieser Bakterien ist weitestgehend unbekannt. In der vorliegenden Arbeit wurden marine Sedimente mit verschiedenen potenziellen Elektronenakzeptoren versetzt, um die Stoffwechselcharakteristika der Klasse Dehalococcoidia zu identifizieren. Die Kultivierungsexperimente zeigten, dass Dehalococcoidia-Spezies in anoxischem Minimalmedium versetzt mit Wasserstoff und Acetat als Elektronendonor und Kohlenstoffstoffquelle bei 30°C und atmosphärischem Druck erfolgreich kultiviert werden können und dementsprechend nicht strikt barophil sind. Zur Quantifizierung von Dehalococcoidia-Spezies wurde ein qPCR-Verfahren entwickelt. Vereinzelt wurde in den Labormikrokosmenansätzen ein Anstieg der ...